Ecodistricts - principles of planning and designing based on case studies - Rama, Bardhyl; Bardhyl Rama (České vysoké učení technické v Praze, 2023)
Through detailed analysis of the selected case studies, this thesis examines ecodistricts, which are city components that bear the load of offering the solutions that the cities themselves, due to their complex and rather complicated structure and organization, can not offer. This thesis focuses on the ecodistricts as a concept of sustainable development, their particular role on finding balanced elements that enable high quality of life for residents and at the same time are in line with the climate neutral goals that the society is pursuing. Although there has been enormous technological development, and certainly many cities have harnessed any possible benefits, there are still limitations to the extent that technological innovations have been applied. But, at the same time there is a huge potential that cities can tap into in their path towards a sustainable and green future. Therefore, this thesis draws upon specific aspects of the ecodistrict structure that contribute to green solutions. Aspects that have been taken into consideration and given a great deal of analysis in this study are general data, urban planning approach, architectural approach, energy, mobility, public spaces and landscape. Every single one of these components has been analyzed for each case study, and later on synthesized for all three case studies. The selected ecodistrict sites represent cases that are globally acclaimed models that successfully integrated architectural innovation, high values in sustainability approach, carbon neutral transportation and energy efficiency and renewable energy solutions, highly focused on livability, air quality and green spaces, among many others. This thesis discusses and explores three overarching and interconnected research questions. Drawing from the case studies evaluation, which key urban and architectural categories and indicators can be taken into consideration for preparing principles of planning and designing ecodistricts? How should ecodistricts be designed? Based on the lessons learned, which principles serve as a baseline for ecodistricts planning and designing? The thesis addressed the first question by listing and elaborating several urban and architectural categories and their sets of indicators, whereas the last two questions through thorough analysis of principles of planning and designing of ecodistricts. The main outcomes that have been presented in this thesis are the detailed results from the analyses of each category and its respective indicators. This should provide solid data to experts, architects and design community when planning and developing ecodistricts. The outcome explores in great detail the potential of categories and indicators combined with new tools and technologies in realizing the ecodistricts and cities of the future, a built environment completely in line with carbon free goals and ecofriendly pathways. The results of the technical conclusions include many advantages and disadvantages detailed in principles of planning and designing of ecodistricts. Those included suggestions about the general data, on site conditions, area, population; about urban planning, on position, blocks, density, height, mix-use; about architectural, on building design and building owners; about energy, on low-energy and passive house buildings, bio based and wind power; about mobility, on public transportation, roads, garages, bikes and pedestrians; about public spaces, on public squares and other functions; about landscape, on green spaces, green roofs, rainwater, and green gardening. Each indicator and category has been given relevant prominence and elaboration based on the case studies. Finally, through this detailed exploration of how ecodistricts are planned, designed and implemented the thesis outcome fulfills the overaching goal to offer new knowledge on the topic, with the hopes and motivation that this knowledge will be practically utilized when developing future ecodistricts.

Through detailed analysis of the selected case studies, this thesis examines ecodistricts, which are city components that bear the load of offering the solutions that the cities themselves, due to their complex and rather complicated structure and organization, can not offer. This thesis focuses on the ecodistricts as a concept of sustainable development, their particular role on finding balanced elements that enable high quality of life for residents and at the same time are in line with the climate neutral goals that the society is pursuing. Although there has been enormous technological development, and certainly many cities have harnessed any possible benefits, there are still limitations to the extent that technological innovations have been applied. But, at the same time there is a huge potential that cities can tap into in their path towards a sustainable and green future. Therefore, this thesis draws upon specific aspects of the ecodistrict structure that contribute to green solutions. Aspects that have been taken into consideration and given a great deal of analysis in this study are general data, urban planning approach, architectural approach, energy, mobility, public spaces and landscape. Every single one of these components has been analyzed for each case study, and later on synthesized for all three case studies. The selected ecodistrict sites represent cases that are globally acclaimed models that successfully integrated architectural innovation, high values in sustainability approach, carbon neutral transportation and energy efficiency and renewable energy solutions, highly focused on livability, air quality and green spaces, among many others. This thesis discusses and explores three overarching and interconnected research questions. Drawing from the case studies evaluation, which key urban and architectural categories and indicators can be taken into consideration for preparing principles of planning and designing ecodistricts? How should ecodistricts be designed? Based on the lessons learned, which principles serve as a baseline for ecodistricts planning and designing? The thesis addressed the first question by listing and elaborating several urban and architectural categories and their sets of indicators, whereas the last two questions through thorough analysis of principles of planning and designing of ecodistricts. The main outcomes that have been presented in this thesis are the detailed results from the analyses of each category and its respective indicators. This should provide solid data to experts, architects and design community when planning and developing ecodistricts. The outcome explores in great detail the potential of categories and indicators combined with new tools and technologies in realizing the ecodistricts and cities of the future, a built environment completely in line with carbon free goals and ecofriendly pathways. The results of the technical conclusions include many advantages and disadvantages detailed in principles of planning and designing of ecodistricts. Those included suggestions about the general data, on site conditions, area, population; about urban planning, on position, blocks, density, height, mix-use; about architectural, on building design and building owners; about energy, on low-energy and passive house buildings, bio based and wind power; about mobility, on public transportation, roads, garages, bikes and pedestrians; about public spaces, on public squares and other functions; about landscape, on green spaces, green roofs, rainwater, and green gardening. Each indicator and category has been given relevant prominence and elaboration based on the case studies. Finally, through this detailed exploration of how ecodistricts are planned, designed and implemented the thesis outcome fulfills the overaching goal to offer new knowledge on the topic, with the hopes and motivation that this knowledge will be practically utilized when developing future ecodistricts.
Ecodistricts – principles of planning and designing based on case studies
Keywords: ecodistricts; econeighborhoods; ecocities; design principles; categories and indicators; sustainable architecture; Sustainable Development Goals (SDGs); climate change; ecodistricts; econeighborhoods; ecocities; design principles; categories and indicators; sustainable architecture; Sustainable Development Goals (SDGs); climate change